2009
DOI: 10.1530/rep-09-0122
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate prevents aging of mouse oocytes

Abstract: Inhibiting oocyte aging is important not only for healthy reproduction but also for the success of assisted reproduction techniques. Although our previous studies showed that cumulus cells accelerated aging of mouse oocytes, the underlying mechanism is unknown. The objective of this paper was to study the effects of pyruvate and cumulus cells on mouse oocyte aging. Freshly ovulated mouse cumulus-oocyte complexes (COCs) or cumulus-denuded oocytes (DOs) were cultured in Chatot-Ziomek-Bavister (CZB) medium or COC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 77 publications
6
55
0
Order By: Relevance
“…When the time of aging progressed to 24 h of hCG injection, AcH3K14 was also detected and displayed an increase of fluorescence signals in the oocytes. Our observation was further confirmed by Liu et al [51] who found that AcH3K14 and AcH4K12 showed an increase in acetylation in mouse oocytes during postovulatory aging. Although unlike mouse oocytes, AcH4K12 was acetylated in mature porcine oocytes, its acetylation level increased during postovulatory aging [52].…”
Section: Histone Acetylationsupporting
confidence: 90%
“…When the time of aging progressed to 24 h of hCG injection, AcH3K14 was also detected and displayed an increase of fluorescence signals in the oocytes. Our observation was further confirmed by Liu et al [51] who found that AcH3K14 and AcH4K12 showed an increase in acetylation in mouse oocytes during postovulatory aging. Although unlike mouse oocytes, AcH4K12 was acetylated in mature porcine oocytes, its acetylation level increased during postovulatory aging [52].…”
Section: Histone Acetylationsupporting
confidence: 90%
“…A decrease in fertilization rate has been associated with aged oocytes in many species including the humans (Lash & Whittaker 1974), mice (Marston & Chang 1964, Liu et al 2009b, cows (Chian et al 1992) and pigs (Kikuchi et al 2000). This phenomenon can be attributed to multiple biochemical and functional alterations to the oocyte that accumulate with post-ovulatory age.…”
Section: Decreased Fertilization Ratementioning
confidence: 99%
“…Following these observations, it has been hypothesized that cumulus cells secrete soluble/ paracrine factor(s) that promote post-ovulatory ageing, potentially an event that coincides with the entry of the cumulus cells into apoptosis . Additionally, the accelerated depletion of the oocyte metabolite pyruvate from culture medium by cumulus cells (Downs et al 2002) appears to directly affect oocyte metabolism and hence post-ovulatory ageing, potentially by causing downstream inhibition of protein synthesis within the oocyte and upsetting redox equilibrium (Liu et al 2009b). …”
Section: Cumulus Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Postovulatory aging-induced abortive SEA deteriorates the egg quality and limits assisted reproductive technologies (ART) such as in vitro fertilization (IVF), intra-cytoplasmic sperm injection (ICSI) and somatic cell nuclear transfer (SCNT) during animal cloning [14,[17][18][19]. Several drugs such as proteasome inhibitor, MG-135 [20,21], melatonin [22], verapamil [16] and pyruvate [23] have been used to prevent postovulatory aging-induced abortive SEA in vitro [16,24].…”
Section: Introductionmentioning
confidence: 99%